If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 6 = 6 + 12x Reorder the terms: 6 + 12x = 6 + 12x Add '-6' to each side of the equation. 6 + -6 + 12x = 6 + -6 + 12x Combine like terms: 6 + -6 = 0 0 + 12x = 6 + -6 + 12x 12x = 6 + -6 + 12x Combine like terms: 6 + -6 = 0 12x = 0 + 12x 12x = 12x Add '-12x' to each side of the equation. 12x + -12x = 12x + -12x Combine like terms: 12x + -12x = 0 0 = 12x + -12x Combine like terms: 12x + -12x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 3.5a=14 | | 6-(-6)=x | | -3x+18=7x-2 | | 3y-3+4y=7 | | 6-(-18)=x | | 2x^2+-x+-3=0 | | m+7=22 | | 6+(-18)=x | | 16x^2+8xy+y^2= | | y=-3x+18 | | 28=4y-6 | | 2m+7=22 | | (6x-2)=56 | | A-3.5=14 | | 5x^2+17x+-12=0 | | e^6x=13 | | 9(-4x+2)=7x | | 2x+30=-2x+2 | | 5x+3y=-29 | | e^3x=13 | | 6x^2+11x+-2=0 | | 5-(-7)=12 | | 5(w+12)= | | 4x-5+3x=9 | | 4q=7q+37 | | 1.5-0.25(a+4)=3+(.05-0.5a) | | 4t^2+18t-400=0 | | -20=-7x+1 | | 5(-4x-3)=13x+9 | | -50-7x=-3x+62 | | 312x+51=33 | | 4c-7=3c |